Optimal under voltage load shedding based on voltage stability index (2016)
This paper presents a methodology for under voltage load shedding using a metaheuristic optimization technique and a stability criterion. Two strategies are proposed to find the minimal size and location of load to shed for the recovery of normal operation conditions. The first one is based on a classical criterion for the under voltage load shedding, identifying the load to disconnect by considering bus voltage level; the second includes a simplified voltage stability index SVSI, which identifies critical buses in the system. The proposed methodology is implemented in an IEEE 14 bus test system, considering a heavy loading condition with andwithout contingency to validate its efficiency.